MIJ821 (onfasprodil) in healthy volunteers: First‐in‐human, randomized, placebo‐controlled study (single ascending dose and repeated intravenous dose) - Baltazar Gomez‐Mancilla; Jeffrey A. Levy; Subramanian Ganesan; Thomas Faller; Gil Issachar; Ziv Peremen; Offir Laufer; Revital Shani‐Hershkovich; Kostas Biliouris; Ela Walker; Mark P. Healy; Oleksandr Sverdlov; et al. (Wiley, 2023)
Abstract This single‐center study administered MIJ821 (onfasprodil) as an intravenous infusion to healthy volunteers and included two parts: a single ascending dose study (Part 1) and a repeated intravenous dose study (Part 2). Primary objective was to evaluate the safety and tolerability of single ascending intravenous doses infused over a 40‐min period and of two repeated doses (1 week apart) of MIJ821 in healthy volunteers. Secondary objectives were to assess the pharmacokinetics of MIJ821 after intravenous infusion in Part 1 and Part 2 of the study. Overall, 43 subjects in Part 1 and 12 subjects in Part 2 were randomized in the study. Median age in Part 1 and Part 2 was 45.0 and 43.5 years, respectively, with the majority being Caucasian (Part 1: 84%; Part 2: 92%). 19 subjects (44.2%) in Part 1 and 8 subjects (66.7%) in Part 2 experienced at least one adverse event (AE). Following single dose in Part 1 and Part 2, the AUCinf values of MIJ821 increased in a dose‐proportional manner across the dose range 0.016-0.48 mg/kg and the Cmax values in a slight overproportional manner across the dose range 0.048-0.48 mg/kg. At the highest dose of 0.48 mg/kg, the geometric mean AUCinf was 708 h ng/mL and the geometric mean Cmax was 462 ng/mL. Inspection of 1‐h post‐dose resting electroencephalography activity across cohorts showed a relationship to administered dose, providing exploratory evidence of distal target engagement. In conclusion, MIJ821 showed a good safety and tolerability profile in healthy volunteers. Dissociative AEs were mild, transient, and dose‐dependent.